2022
DOI: 10.1186/s12943-021-01482-9
|View full text |Cite|
|
Sign up to set email alerts
|

CircNFIB inhibits tumor growth and metastasis through suppressing MEK1/ERK signaling in intrahepatic cholangiocarcinoma

Abstract: Background Considerable evidence shows that circular RNAs (circRNAs) play an important role in tumor development. However, their function in intrahepatic cholangiocarcinoma (ICC) metastasis and the underlying mechanisms are incompletely understood. Methods circNFIB (hsa_circ_0086376, termed as cNFIB hereafter) was identified in human ICC tissues through circRNAs sequencing. The biological role of cNFIB was determined in vitro and in vivo by gain or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 92 publications
0
18
0
Order By: Relevance
“…Furthermore, the abnormal regulation of kinase and phosphatase signaling pathways plays a principal role in oncogenic pathway activation in numerous cancers [ 6 , 7 ]. Previous research demonstrated that ERK signaling modulation inhibits CCA proliferation and metastasis [ 8 ]. Moreover, the suppression of VEGFR2 phosphorylation levels reduces the PI3K/AKT signaling pathway, resulting in alterations in CCA cell proliferation, apoptosis, and invasion [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the abnormal regulation of kinase and phosphatase signaling pathways plays a principal role in oncogenic pathway activation in numerous cancers [ 6 , 7 ]. Previous research demonstrated that ERK signaling modulation inhibits CCA proliferation and metastasis [ 8 ]. Moreover, the suppression of VEGFR2 phosphorylation levels reduces the PI3K/AKT signaling pathway, resulting in alterations in CCA cell proliferation, apoptosis, and invasion [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nfib encodes nuclear factor 1 B-type (NF1-B), which is relatively highly expressed in the mouse heart and is involved in DNA replication, transcription and transcription regulation [ 11 ]. Du et al found that circNFIB may be used as a biomarker for intrahepatic cholangiocarcinoma (ICC) patients, and the circNFIB-MEK-ERK axis may be a potential therapeutic target for ICC treatment [ 37 ]. In addition, a recent study reported that circNFIB plays a critical role in improving cardiac fibrosis in vivo and in vitro in an MI model [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, circNFIB was demonstrated to repress the metastasis and growth and promote trametinib sensitivity in ICC by blocking MEK1/ERK pathway. 19 Xu et al showed that high circHMGCS1-016 was associated with recurrence and unfavorable prognosis of ICC patients, and showed an immunosuppressive role to contribute to immune tolerance by reducing CD8 + T cells infiltration in ICC. 20 Thus, circRNAs have great potential as biomarkers for ICC molecular therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, circNFIB was demonstrated to repress the metastasis and growth and promote trametinib sensitivity in ICC by blocking MEK1/ERK pathway. 19 Xu et al…”
Section: Discussionmentioning
confidence: 99%